Influence of Self-Efficacy and Motivation on Work Readiness in Vocational Education Students - Sonny Taufan; Aulia Rosalinda Baladika Jayanti; Dewi Susita; Eka Legya Frannita (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The increasing demand for skilled workers in Indonesia’s competitive job market highlights the importance of preparing vocational students for employment. This study aims to investigate the influence of self-efficacy and motivation on work readiness among vocational students in Jakarta, Banten, and Bogor. A cross-sectional design was employed, involving 336 final-year students from polytechnic programs selected through purposive sampling. Data were collected using an online questionnaire with a 5-point Likert scale, measuring self-efficacy, motivation, and work readiness. Multiple linear regression analysis was conducted using SPSS to examine the relationships between these variables. The findings reveal that self-efficacy and motivation individually and collectively have a significant positive impact on work readiness, explaining 62% of the variance in preparedness. Students with high self-efficacy demonstrate strong confidence in their professional capabilities, while motivated students exhibit greater commitment to skill development. These results underscore the critical role of psychological factors in enhancing employability. Vocational institutions should prioritize strategies to boost self-efficacy and motivation, such as hands-on training and industry partnerships, to better prepare students for workforce demands and reduce the skills gap in Indonesia’s job market.